Myoepithelioma of the Soft Palate: a Case Report Giving Special Attention to the Differential Diagnosis - Felipe Fornias Sperandio; Fernanda Salgueiredo Giudice; Décio dos Santos Pinto-Junior; Suzana Cantanhede Orsini Machado de Sousa (eJournal of Oral Maxillofacial Research)
Background: Myoepitheliomas are rare tumours that may generally arise from the minor or major salivary glands. The differential diagnosis of this tumour should be performed along with several benign and malignant soft tissue neoplasms. The present case report describes an asymptomatic mass that arose in the soft palate of 42 year old black woman with duration of the six months.Methods: An incisional biopsy of soft palate lesion was carried out and submitted for histological evaluation under the clinical hypothesis of salivary gland tumour. To confirm the myoepithelial nature of neoplastic cells the immunohistochemical reactions for smooth-muscle actin, cytokeratins and S100 were performed.Results: The histological examination revealed the presence of tumour originating from a minor salivary gland and covered by a stratified squamous oral epithelium. The tumour cells were arranged in order to form a myxoid pattern and, individually, small and/or medium spindle-shaped cells with predominantly round or ovoid nuclei, as well as epithelioid and plasmocytoid cells were noted. The stroma was myxomatous and no ductal or syringomatous epithelial structures were observed. Following the histological and immunohistochemical diagnosis of myoepithelioma, the lesion was surgically removed. After the surgery, a follow-up of one year showed no signs and symptoms of reccurrence.Conclusions: The myoepithelioma should be carefully distinguished from the other soft tissue tumours, especially those arising from salivary glands, such as pleomorphic adenoma and adenoid-cystic carcinoma.